Effect of quasi-hydrostatic extrusion on microhardness in CuCrZr alloy - Belyaeva, A. I.; Galuza, A. A.; Khaimovich, P. A.; Kolenov, I. V.; Savchenko, A. A.; Ryzhkov, I. V.; Shtan, A. F.; Solodovchenko, S. I.; Shulgin, N. A. (National Science Center "Kharkiv Institute of Physics and Technology", 2015)
Effect of quasi-hydrostatic extrusion at liquid nitrogen (77 K) and room (300 K) temperatures on the microhardness in high-strength CuCrZr alloy has been investigated. It is shown that the combination of equalchannel angular compression (ECAP) and quasi-hydrostatic extrusion (QHE) allows raising microhardness of CuCrZr alloy especially in the case of the low-temperature (77 K) QHE treatment.

Досліджено вплив квазігідроекструзії при температурі рідкого азоту (77 K) та кімнатній температурі (300 K) на мікротвердість жароміцного CuCrZr-сплаву. Визначено, що комбінація рівноканального кутового пресування (РККП) та квазігідроекструзії (КГЕ) призводить до підвищення мікротвердості CuCrZr-сплаву, особливо у випадку низькотемпературної (77 K) КГЕ-обробки.
Вплив квазігідроекструзії на мікротвердість сплаву CuCrZr
Keywords: quasi-hydrostatic extrusion; liquid nitrogen; microhardness; quasi-hydrostatic extrusion; квазігідроекструзії; рідкий азот; мікротвердість; сплави